DESIGN AND IMPLEMENTATION OF REAL TIME PAPER DYNAMICS AND TEARING SIMULATION USING SPRING-MASS MODEL - WIWOHO (NIM: 23207163), ALVANI
Physics implementation in video games brought new level of interactivity, immersion and reality while playing in virtual world. Rigid body dynamics simulate the force and gravity applied to the object so it can move and behave similiar to the real world. Soft body dynamics which gained developer interest in the last few years could simulate deformable object improving rigid body simulation that only support non-deformable model. This improvement took the soft body objects such as cloth, hair, and rubber to the real time simulation. Spring mass model is a simulation method that widely used to simulate soft body objects. This model is using mass points that connected to each other by springs. The spring nature of this implementation could make the object compressed or extended if exerted by a certain force. The oscillation generated by springs make this model is perfect match for simulating rubbery objects. Paper dynamics and tearing simulation could be performed by using spring mass model. The grid structure of spring mass naturally support the tearing since it defined as geometric operation. The problem that arise is the paper dynamics behavior which is much stiffer than cloth or rubber. Several methods have been developed to overcome this problem such as increasing the stiffness of each spring or adding constraints to spring length. This thesis will discuss the methods, algorithms, and implementation to simulate paper dynamics and tearing by using spring mass model.